(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Dadru is one of the most common dermatological conditions encountered in clinical practice. Most of skin diseases in Ayurveda are described under the heading of Kushta. In general clinical practice around 10-20% patients suffer from skin disorders and out of them, fungal infections constitute up to 20%. Dadru is a variety of Kushta with Rasa, Rakta and Mamsadhatu involvement, manifesting with Kandu, Mandala, Ruja, Raaga, Rookshata and Pidaka. Chakramarda possesses Katu rasa, Laghu, Rukshaguna, Kapha Vatahara, Varnya, Vishagna, Vranaropana and Kushtagna properties. Chakramardhataila is an Anuboota yoga employed in management of Dadrukushta. Current study includes 42 Patients from O.P.D. of S.D.M. College of Ayurveda and Hospital, Hassan diagnosed to have Dadrukushta based on signs and symptoms. Therapeutic effect was evaluated before, in between and after treatment. The present clinical study has shown Symptoms of Kandu, Raaga and Twakrukshata reduced after application of Chakramarda taila, which were statistically highly significant with P value 0.001. Symptoms of Uthsanna mandala reduced after application of Chakramarda taila. It was also statistically significant with P value 0.002. Pidaka between before treatment to after treatment showed reduction with P value 0.005 which is statistically significant. After Chakramarda taila application on lesion of Dadru Kushta has demonstrated decrease in pathognomonic signs and symptoms Kandu, Raga, Twakrukshata which was statistically highly significant with P value 0.001 and reduction in Uthsanna mandala, Pidaka which is statistically significant. Hence, application of Chakramarda Taila is an effective treatment modality in management of Dadru Kushta.